Wellbeing in our own words: survivors of slavery defining wellbeing - Dang, Minh (2021)
The anti-slavery movement is witnessing survivors of slavery call for a new moral obligation: to co-construct a survivor’s journey in freedom after enslavement. To the extent that survivors of slavery are the focus of research, current evidence enumerates the deleterious effects of slavery on an individual’s physical, social, and psychological health. Evidence of survivors’ wellbeing is sparse, with few studies exploring the presence of positive attributes demonstrated by survivors of slavery. While understanding the negative health consequences is important for efforts to diminish survivors’ suffering, public advocacy efforts by survivors have called for interventions that enable a full life, one that is more than the absence of enslavement and its consequences. To respond to survivors’ requests and fill a gap in anti-slavery research, this thesis asked and answered: how do survivors of slavery define wellbeing?